DEVELOPMENT OF THE EXTERNAL ENERGY POLICY OF THE EUROPEAN UNION - N. Y. Kaveshnikov (Vestnik MGIMO-Universiteta)
The article analyses development of external energy policy of the European Union (EU). In spite of the Lisbon treaty didn’t substantially expend EU powers in external energy policy, European Commission (EC) became more active in recent years. Decision on exchange of information about bilateral energy agreements between Member States (MSs) and third countries may deprive producers of opportunity to differentiate terms of infrastructure projects and energy supply in different MSs. European Commission participation in MSs negotiations with third countries as a guardian of energy market provisions will inevitably increase negotiation power of MSs. Nevertheless, only smooth and modest extension of powers of the EC would be possible because of opposition of numerous countries which makes a search of consensus very difficult. Among priority activities of the EU external energy policy one could identify ‘export’ of energy market provisions in neighbor countries; diversification of suppliers and prioritization of politically selected supply routes; dramatic increase of regulatory activity at EU level. All these activities are partially successful, but they all have some shortages. Several EU legislative and regulatory measures risk to run counter to existing obligations of MSs.